Pemanfaatan Limbah Kotoran Sapi untuk Produksi Batu Bata Ramah Lingkungan dan Tahan Gempa - Sukamta, Sukamta; Widyasmoro, Widyasmoro; Wahyuni, Fitri; Budiyantoro, Cahyo; As’ari, Muhammad Agung; Atikasari, Tiara Cahya; Agustina, Nurhaliza; Harahap, Yudani Alamsyah (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2020)
Cow dung waste at Srunen hamlet, Glagaharjo village, Cangkringan, Sleman is recorded to be high in quantity since it also has a high population of dairy cows. The high volume of cow dung waste leads to environment pollution, either water or air pollution. The environment pollution it causes may further trigger some problems regarding society’s health, safety and comfort. Thereby, the abundant quantity of cow dung waste needs to be well-managed and oriented for economics. One of among other technologies to manage cow dung waste which had never been implemented before is to utilize the waste as the raw material component of brick. Such brick production technology is not only environmentally friendly but is also resistant toward earthquake. This technology was introduced and implemented during the Community Service program at Glagaharjo village. The program was implemented through the methods of assessment and education, as well as feasibility test. Training and practice were conducted to adopt the technology of environmentally friendly and earthquake resistant cow dung brick. Further, the product was tested for its feasibility as construction material. The success of the program is shown from the society’s ability to produce the environmentally friendly and earthquake resistant brick which has also increased society’s income and the hamlet’s economy